Environment adaptive hydrogels for extreme conditions: a review. Issue 4 (12th December 2019) - Jiang, Yanan; Lu, Xiong
Abstract : Hydrogels have attracted extensive attention due to their excellent swellability, permeability, and biocompatibility. In recent years, the demand for multifunctional hydrogels has been on the increase; there is also an increased need to utilise hydrogels in more varied and extreme applications, such as low temperature, anoxic environment, ultraviolet damage, burns, and the marine environment. Furthermore, traditional hydrogel materials cannot meet the requirements of the application in extreme environments. Therefore, it is necessary to design and develop hydrogels that are adaptable to certain extreme conditions. This review summarises recent advances in hydrogels that meet application requirements under extreme conditions, particularly in the biomedical field and prospects for their future development.